Trans-imperial celebrities. On the road with the first Katangese guitar stars of the 1950s - (:unkn) unknown (My University, 2022)
This article considers the emergence of African musical celebrities within the post-1945 context of the development of radio, the recording industry and ethnomusicology. It explores the notion of “trans-imperial celebrity” from the perspective of guitarists Jean Bosco Mwenda and Édouard Masengo who became the first stars of Eastern Belgian Congo and were some of the most mobile artists of the continent in the 1950s. Originally from Katanga, a region at the crossroads of musical influence from Léopoldville (Kinshasa) and Johannesburg, they entered and opened new music circuits in Congo, South Africa and Kenya. The article retraces their “circulatory territories”, highlighting a little-known part of the social and cultural history of this trans-imperial space. It thus shows how early mediatic celebrity extended the routes of popular musicians whose way of life was based on an ancient culture of itinerancy.
Keywords: African Research